The Influence Of Green Governance, Green Competitive Advantage, Green Investment And Green Innovation On Company Value Automotive Sector On BEI - Yuniep Mujati Suaidah (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This research aims to analyze whether green governance, green competitive advantage, green investment and green innovation have a positive effect on company value in automotive sector companies listed on the IDX. This research adopts a quantitative approach.  The focus of the research is automotive companies listed on the IDX from 2021 to 2023. According to www.ajaib.co.id, there are 16 automotive companies listed on the IDX. This research uses a saturated sample. Types of secondary data. Data collection techniques with documentation on the website www.idx.com. Data analysis uses multiple linear regression. Green governance has a significant positive effect on the value of automotive sector companies listed on the stock exchange. Green competitive advantage has a significant positive effect on the value of automotive sector companies listed on the stock exchange. Green investment has a significant positive effect on the value of automotive sector companies listed on the stock exchange. Green innovation has a significant positive effect on the value of automotive sector companies listed on the stock exchange.